DEVELOPMENT OF SUSTAINABLE MOTIVATION OF FUTURE PRIMARY SCHOOL TEACHERS IN THE THREE-SUBJECT DIDACTIC MODEL (IN WARTIME CONDITIONS) - Petukhova Любов; Volianiuk Анастасія (Journal of Information Technologies in Education (ITE), 2023)
The article examines the peculiarities of the development of sustainable motivation of future primary school teachers in the model of three-subject didactics in wartime. Features of distance learning in institutions of higher education as a security measure in war conditions are highlighted. The focus is on the difficulties students and teachers face during online learning. The leading motives of online education are analyzed, the results of research on demotivating factors, ways to eliminate or reduce them are highlighted. The specified study of demotivating factors was conducted in 2 stages: in 2020-2022 in the pre-war period and in April 2022 during the war on the basis of the Kherson State University among applicants of the specialty 013 Primary education. Within the framework of the study, a questionnaire was conducted among students of 1-4 courses of the first (bachelor) level of higher education. On the basis of the analysis of existing trends and changes, conclusions were made and practical advice was given to eliminate demotivating factors in the educational process of the institution of higher education. The article defines the real role of the pedagogue (teacher of a higher education institution / school teacher, etc.) in the information society. The necessary conditions for the existence of an environment that contributes to the achievement of learning outcomes are highlighted. The role of the information and communication pedagogical environment in the conditions of war in the context of increasing the level of sustainable motivation is characterized. The article focuses on the reconstruction of the psychological and pedagogical structure of the teacher’s activity in the process of implementing information and communication technologies. The results of the analysis of the compliance of the key principles of the Agile methodology in education and the priorities of the information and communication pedagogical environment in the model of three-subject didactics are highlighted. The influence of self-regulated and project-oriented learning on the development of the student’s motives, the possibility of their implementation, guided by the model of three-subject didactics, is characterized.